Hero, Traitor, Daughter (Of Crowns and Glory-Book 6) - Morgan, Rice (Lukeman Literary, 2017)
"Morgan Rice has come up with what promises to be another brilliant series, immersing us in a fantasy of valor, honor, courage, magic and faith in your destiny. Morgan has managed again to produce a strong set of characters that make us cheer for them on every page....Recommended for the permanent library of all readers that love a well-written fantasy." --Books and Movie Reviews, Roberto Mattos (regarding Rise of the Dragons) HERO, TRAITOR, DAUGHTER is book #6 in Morgan Rice's bestselling epic fantasy series OF CROWNS AND GLORY, which begins with SLAVE, WARRIOR, QUEEN (Book #1). 17 year old Ceres, a beautiful, poor girl from the Empire city of Delos, wakes to find herself powerless. Poisoned by the sorcerer's vial, held captive by Stephania, Ceres life reaches a low point as she is made cruel sport of-and is unable to do anything to stop it. Thanos, after killing his brother Lucious, embarks for Delos, to save Ceres and to save his homeland. But the Felldust fleet has already set sail, and with the might of the world bearing down on it, it may be too late to save everything he holds dear. An epic battle ensues, one that may determine the fate of Delos forever. HERO, TRAITOR, DAUGHTER tells an epic tale of tragic love, vengeance, betrayal, ambition, and destiny. Filled with unforgettable characters and heart-pounding action, it transports us into a world we will never forget, and makes us fall in love with fantasy all over again. "An action packed fantasy sure to please fans of Morgan Rice's previous novels, along with fans of works such as The Inheritance Cycle by Christopher Paolini.... Fans of Young Adult Fiction will devour this latest work by Rice and beg for more." --The Wanderer, A Literary Journal (regarding Rise of the Dragons) Book #7 in OF CROWNS AND GLORY will be released soon!
Keywords: Sci-fi, fantasy; Dobrodružství, napětí, fantasy